STRATEGI PENGELOLAAN SUNGAI CIBANTEN PROVINSI BANTEN BERDASARKAN ANALISIS DAYA TAMPUNG BEBAN PENCEMARAN AIR DAN KAPASITAS ASIMILASI - Baherem Baherem; Suprihatin Suprihatin; Nastiti Siswi Indrasti (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2014)
Cibanten river is one of the most potential to be developed as a source of raw water. Crucial issues at Cibanten river is the increasing load of water pollution as indicated by parameter BOD, COD and TSS. This study aimed to estimate the amount of Total Maximum Daily Load (TMDL) in Cibanten river, analyze the quality Status of the Cibanten river water, analyze the capacity of assimilation, and determine management strategy of Cibanten river of Banten Province. TMDL of BOD were determined by modeling Qual2KW and the results were compared with the second class water quality standards to regulation No. 82/2001. Management strategy of Cibanten river determined by analysis of the results of an expert survey method with AHP (Analytical Hierarchy Process). Quality Status of the Cibanten river water with pollution index was light raiment and storet method of Raw Water Quality class II belong was heavy raiment. Results of the simulation calculation of TMDL, the total load of pollution in the Cibanten BOD was730 tons/month while the TMDL of BOD was 146.801 tons/month. Results of the analysis of assimilation capacity COD was 24208 tons/month. Results of the analysis methods of survey expert with AHP (Analytical Hierarchy Process) is monitoring and surveillance as an alternative management strategies with the highest priority of the Cibanten river (agregate value 0.202) and following up the monitoring results.Keywords: Cibanten River, total maximum daily loads, Qual2Kw, assimilation capacity, storet, pollution index, Analytical Hierarchy Process